EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING TERHADAP KEMAMPUAN PROBLEM SOLVING ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL PARANGTAMBUNG - Khusnul Khatimah; Herman; Andi Sri Wahyuni Asti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the Project-Based Learning (PjBL) model on the problem-solving ability of 5-6-year-old children in Aisyiyah Bustanul Athfal Parangtambung Kindergarten. The primary issue addressed in this study is the children's low capability to identify problems and find solutions independently. The approach applied in this study was quantitative with a quasi-experimental design. The research sample consisted of 24 children divided into two groups: the experimental group (12 children) treated with the PjBL model through the